Food and Feeding Habits of Johnius carutta (Bloch, 1793) off Visakhapatnam, East-coast of India - Swamy Kumar, M.; Rajeswari, G.; Kishore, B. (Fishery Technology, 2015)
Specimens of Johnius carutta (Bloch, 1793) collected from off Visakhapatnam during 2008-09 were used for gut content analysis. J. carutta was observed to be euryphagic, carnivorous, benthic, moderate feeder feeding mostly on teleost fish, free living crustaceans, polychaetes and molluscs. Analysis of gut revealed contents different food items with dominance of squilla (17.72%) followed by Acetes spp. (11.40%), shrimps (10.81%), teleost fish (9.10%), polychaetes (7.10%), crabs (5.10%) and crustacean appendages (3.20%). Quantitative analysis revealed the non-penaeid shrimp Acetes spp. (32.51%) dominating the food items followed by squilla (15.20%), shrimp,Â (11.50%), fish (9.73%), polychaetes (8.63%), crustacean appendages (6.10%) and crab (3.90%). The composite index values indicated that squilla (35.62) is the most preferred food followed by Acetes spp. (18.03), teleost fish (16.62), shrimp (10.38) and polychaetes (6.26). The average gastro-somatic index values are relatively low during pre-monsoon (1.27%), moderate during monsoon (1.74%) and relatively high during post-monsoon (1.95%).